Enhancing the Competence of Indonesian Language Teachers through Mentoring in Scientific Publications Based on the Open Journal System - Rianto Rianto; Tato Nuryanto; Arifin Nasa; Dimas Diantoro (Universitas Lambung Mangkurat, 2024)
This article discusses the importance of mentoring in scientific publications for Indonesian language teachers, focusing on using the Open Journal System (OJS) system for publishing research results as an output. Scientific publications by Indonesian language teachers not only enhance individual reputations but also make valuable contributions to developing the scientific field of Indonesian language learning. This research explains the mentoring process followed by Indonesian high school teachers in Cirebon Region 3 in scientific publications and the process of using OJS by teachers in mentoring scientific publications. The method applied in this service is the Participation Action Research method. The results of the community service show that teachers actively participate in training and mentoring to enhance understanding regarding writing scientific articles, while teachers can create accounts and submit research articles to OJS.